Modeling of ordered-disordered transition in two dimensional binary compound: Monte carlo simulation of interface characteristic - Yongyut Laosiritaworn (2018)
In this study, Monte Carlo simulations were used to investigate the ordered-disordered transition behavior of a two dimensional binary compound represented by Ising spins on square lattice. The spin exchange Kawasaki algorithm was use to update the system. With varying the system temperature and adhesive interaction strength, while keeping the cohesive interaction fixed, the system morphologies were investigated via the cluster (of the same spin) forming and the interface/surface area of the cluster. The results show that ferro-favorable systems exist only two large clusters (of the two binary species) at low temperatures. However, with increasing the temperature, the clusters reduce in size while their interface/surface area grows, becomes maximum and drop. This is due to the competitive effect between energy minimization by reducing the cluster size and the thermodynamic kinetic energy in diffusing Ising spins into random fashion. In addition, by increasing the adhesive interaction strength, even the ferro-type cluster forms, the cluster becomes smaller due to the introduction of anti-bonding between spins caused by stronger adhesive interaction. Diagrams of these phenomena which displays relationship among adhesive interaction, temperature, and the cluster of the same spin characteristic as well as the interface/surface area were given. These diagrams can be used as guides in enhancing the topic in acquiring desired applications having parts made from binary compound in which the interface characteristic is important. © 2014 Taylor & Francis Group, LLC.